Strength of motivation and academic performance of medical students: a longitudinal study - Sandeep Bansal; Kelly Pagidas (BMC Medical Education)
Abstract Background The strengn for medical school reflects a student’s perseverance in continuing medical training, regardless of personal sacrifices and academic or situational setbacks. Recognizing the patterns of changes in the strength of motivation may be beneficial in pinpointing the time(s) when students struggle to adapt to the rigors of the training, allowing educators to provide appropriate support. We examined the strength of motivation longitudinally and its association with examination performance during the basic science and core clerkship periods. Methods A prospective longitudinal cohort study was conducted at the Burnett School of Medicine from November 2020 through November 2023. First-year medical students were enrolled in the study (n = 51). The Strength of Motivation for Medical School-Revised version (SMMS-R) questionnaire, which consists of three subscales (Willingness to Sacrifice, Readiness to Start, and Persistence), was used at four distinct points during the preclinical and core clinical training. We compared the SMMS-R scores across four measurement points. Average scores from sets of summative assessments corresponding to the SMMS-R data collection time points were used to study correlation with SMMS-R scores. Results A repeated-measures ANOVA with Wilks’ lambda determined a significant effect of time on the mean composite SMMS-R scores (p < 0.001), with a medium effect size ( $$\:{η\:}_{\text{p}}^{2}$$ = 0.11). Subscale scores of Willingness to Sacrifice and Persistence showed significant variation in the strength of motivation across time with a medium effect size, p = 0.015, $$\:{η\:}_{\text{p}}^{2}$$ = 0.07 and p = 0.007, $$\:{η\:}_{\text{p}}^{2}$$ = 0.08, respectively. Examination performance varied significantly over time (p < 0.001), with a large effect size ( $$\:{η\:}_{\text{p}}^{2}$$ = 0.16). However, no significant correlation was found between the SMMS-R and examination scores. Conclusion Students often enter medical school with high levels of motivation, yet their strength of motivation may fluctuate as they encounter the realities and rigor of the curriculum. Results from our study revealed a significant decline in the strength of motivation and examination performance as medical students advanced in basic science and core clinical training. Our findings can inform the implementation of student-supporting mechanisms that could help sustain original (or higher) levels of strength of motivation as medical students advance in their training.